2020
DOI: 10.3390/atmos11040362
|View full text |Cite
|
Sign up to set email alerts
|

What Polarimetric Weather Radars Offer to Cloud Modelers: Forward Radar Operators and Microphysical/Thermodynamic Retrievals

Abstract: The utilization of polarimetric weather radars for optimizing cloud models is a next frontier of research. It is widely understood that inadequacies in microphysical parameterization schemes in numerical weather prediction (NWP) models is a primary cause of forecast uncertainties. Due to its ability to distinguish between hydrometeors with different microphysical habits and to identify “polarimetric fingerprints” of various microphysical processes, polarimetric radar emerges as a primary source of needed infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 112 publications
(242 reference statements)
0
15
0
Order By: Relevance
“…The WRF model version 4.1.3 (Skamarock et al, 2019) is used to simulate the tropical oceanic MCS event on 26 May 2015. Two one-way nested domains with 3 and 1 km horizontal grid spacing and 51 vertical levels are adopted (Fig.…”
Section: Model Setupmentioning
confidence: 99%
“…The WRF model version 4.1.3 (Skamarock et al, 2019) is used to simulate the tropical oceanic MCS event on 26 May 2015. Two one-way nested domains with 3 and 1 km horizontal grid spacing and 51 vertical levels are adopted (Fig.…”
Section: Model Setupmentioning
confidence: 99%
“…Examples that have been heavily used are radar simulators that include polarimetry and velocity ( 66 68 ) and satellite simulators that include infrared and passive microwave ( 69 – 71 ). These simulators support model evaluations targeting specific processes, particularly microphysical processes, that produce “fingerprints” in observations ( 72 ) that can be used to better understand and constrain processes and properties ( 73 , 55 ).…”
Section: Methods For Blending Observations and Modelsmentioning
confidence: 99%
“…The error of the log(N t ) estimate varies between 0.7 and 1.0 (in log units). A more detailed discussion on the accuracy of the polarimetric retrievals ( 5)-( 10) can be found in Ryzhkov and Zrnic (2019), Ryzhkov et al (2020), and Bukovcic et al (2018Bukovcic et al ( , 2020.…”
Section: Radar Microphysical Retrieval Algorithmsmentioning
confidence: 99%
“…The radar retrieval equations for computing microphysical variables in rain and ice which we utilize in our study can be found in Ryzhkov and Zrnic (2019, Chapter 11), Ryzhkov et al. (2020), Bukovcic et al. (2018, 2020), and Carlin et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation